Estimated COVID-19 Periodicity and Correlation with SARS-CoV-2 Spike Protein S1 Antigenic Diversity, United States - Erica Billig Rose; Clinton R. Paden; Peter W. Cook; Kevin C. Ma; Amber Winn; Juan Castro; Lakshmi Panagiotakopoulos; Benjamin J. Silk (Emerging Infectious Diseases)
Emergence of antigenically diverse SARS-CoV-2 variants may be correlated with temporal circulation patterns. We analyzed positive SARS-CoV-2 tests in the United States reported to a national, laboratory-based surveillance network and unique amino acid sequences of the S1 region of the spike protein reported to national genomic surveillance during October 2020–September 2024. We estimated SARS-CoV-2 dominant periodicities using a discrete Fourier transform, described S1 variation using the Simpson diversity index (SDI), and estimated Spearman cross-correlation coefficients between percentage change in SDI and percentage positivity. SARS-CoV-2 activity consistently peaked during July–September and December–February, and dominant periodicities were at weeks 52.2 and 26.1. Percentage positivity and percentage change in SDI were negatively correlated (ρ = −0.30; p<0.001). SARS-CoV-2 peaks occurred in late summer and winter, a pattern likely related to rapid SARS-CoV-2 evolution and cyclical diversity. Monitoring associations between percentage positivity and SDI can help forecast expected surges and optimize prevention and preparedness.